Right again on restrictions. Here you cross-multiply:
(x-4)(x-4) =6x
x^2 - 8x + 16 = 6x
Subtract 6x to make it = 0
x^2 - 14x + 16 = 0
You can't do FOIL so use the quadratic formula with
a=1, b= -14 and c= 16
14 +- sqrt(196-4x1x16) all over 2x1
14 +- sqrt 132 all over 2
sqrt 132 simplifies to 2 sqrt 33
14 +- 2 sqrt 33 all over 2
That's 7 +- sqrt 33
Check the work
2006-11-27 12:34:48
·
answer #1
·
answered by hayharbr 7
·
1⤊
0⤋
Actually does your original problem look like this?
6.............4
- - 4 = x - -
x..............x
If so, then the answer below is correct.
The only value x can't be is zero, because that would result in zeros in the denominator in the original equation, and that's forbidden.
Multiply both sides by x:
6 - 4x = x^2 - 4
Get everything on one side:
0 = x^2 + 4x -10
Use quadratic formula:
x = [-4 +/- sqrt(16 - 4(1)(-10))]/2(1)
x = [-4 +/- sqrt(56)]/2
x = [-4 +/- sqrt((4)(14)]/2
x = [-4 +/- 2sqrt(14)]/2
x = -2 +/- sqrt(14)
Ugly, but that's the answer, if I didn't mess up.
If instead, the original problem looked like:
6..........x - 4
------ = ------
x - 4......x
(and if it did, you should have written it as 6/(x-4) = (x-4)/x)
Then x can't be equal to 4 or 0, and you do cross-multiply
(x-4)(x-4) = 6x
x^2 - 8x + 16 = 6x
x^2 - 14x + 16 = 0
then use the quadratic on that...
2006-11-27 20:36:46
·
answer #2
·
answered by Jim Burnell 6
·
0⤊
0⤋
x = 0 is the undefined value. With that out of the way...
Multiply everything by x to get rid of the demoninator (I call them demoninators because they are evil) That leaves you with:
6 - 4x = x^2 - 4
0 = x^2 + 4x - 10
x = (-4 +- sqrt(16 + 40))/2 = -2 +- sqrt(14)
2006-11-27 20:36:28
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
6/(x-4) = (x-4)/x
Simplest way is to cross multiply, getting:
(x-4)(x-4) = 6x
x^2 -16X +16 =6x
x^2 - 22x +16 =0
Now use quadratic formula:
x= [22 + or - sqrt( 22^2-4*1*16)]/2
x= [22+ 2sqrt(105)]/2 = 11+ sqrt(105), and
x = 11-sqrt(105)
2006-11-27 20:43:03
·
answer #4
·
answered by ironduke8159 7
·
0⤊
0⤋
You multiplies both sides with x and at the same times notes that x can't be 0 cause x is in the denominator in the original equation and division by zero is undefined.
Now you have yourself a second order equation.
2006-11-27 20:36:24
·
answer #5
·
answered by User1 2
·
0⤊
0⤋
x cannot equal 0 since you cannot divide by 0.
6/x - 4 = x - 4/x
Multiply both sides by x.
6 - 4x = x^2 - 4
0 = x^2 + 4x - 10
x = (-4 +/- sqrt(16 + 40))/2
= -2 +/- sqrt(14)
2006-11-27 20:34:44
·
answer #6
·
answered by Anonymous
·
0⤊
1⤋
(x-4)^2=6x
x^2 + 16 -8x = 6x
X^2 +16 -14x = 0
x = 7 (+or -) sqrt(33)
2006-11-27 20:35:19
·
answer #7
·
answered by Rajkiran 3
·
0⤊
0⤋